Methane and carbon dioxide in dual‐porosity organic matter: Molecular simulations of adsorption and diffusion. Issue 3 (14th August 2020) - Rezlerová, Eliška; Brennan, John K.; Lísal, Martin
Abstract: Shale gas, which predominantly consists of methane, is an important unconventional energy resource that has had a potential game‐changing effect on natural gas supplies worldwide in recent years. Shale is comprised of two distinct components: organic material and clay minerals, the former providing storage for hydrocarbons and the latter minimizing hydrocarbon transport. The injection of carbon dioxide in the exchange of methane within shale formations improves the shale gas recovery, and simultaneously sequesters carbon dioxide to reduce greenhouse gas emissions. Understanding the properties of fluids such as methane and methane/carbon dioxide mixtures in narrow pores found within shale formations is critical for identifying ways to deploy shale gas technology with reduced environmental impact. In this work, we apply molecular‐level simulations to explore adsorption and diffusion behavior of methane, as a proxy of shale gas, and methane/carbon dioxide mixtures in realistic models of organic materials. We first use molecular dynamics simulations to generate the porous structures of mature and overmature type‐II organic matter with both micro‐ and mesoporosity, and systematically characterize the resulting dual‐porosity organic‐matter structures. We then employ the grand canonical Monte Carlo technique to study the adsorption of methane and the competing adsorption of methane/carbon dioxide mixtures in the organic‐matter porous structures. We complement the adsorption studies by simulating the diffusion of adsorbed methane, and adsorbed methane/carbon dioxide mixtures in the organic‐matter structures using molecular dynamics.